Temporal Variability in Heterotrophic Carbon Dioxide Emissions From A Drained Tropical Peatland in Uganda - Farmer, Jenny; Langan, Charlie; Smith, Jo U. (Frontiers in Soil Science, 2022)
Our study measured heterotrophic carbon dioxide (CO2) emissions in a drained peatland under potato cultivation in south-western Uganda. Soil carbon losses have not previously been reported for this land use, and our study set out to capture the range and temporal variation in emissions, as well as investigate relationships with key environmental variables. Soil chamber-based emission measurements were taken over five days at four points in time over the year to capture daily and monthly variability, including day and night sampling to capture any diurnal variations in temperatures and soil flux. Differences in soil microtopography from mounding of soils for potato beds and drainage trenches had a significant effect on the rate of soil flux. Diurnal sampling showed no significant difference in emissions or soil temperatures in the raised potato beds between day and night. More significant effects on soil flux from environmental drivers, such as water table depth, were observed between months, rather than hours and days. There were significant differences in the relationships between environmental variables and soil flux, depending on if soils had been recently disturbed or not. Area-weighted emissions based on microtopography gave a mean annual emissions factor of 98.79  1.7 t CO2 ha-1 y-1 ( standard error) from this peatland use.